(untitled) (Hà Nội, 2010)
This paper presents the main findings (both methodological and analytical) of these two rounds of surveys as regards the informal sector in Hanoi and HCMC. In the context of the global crisis, it looks at the dynamics of the informal sector between 2007 and 2009. Taking advantage of this unique survey protocol, the first part investigates the macro dynamics comparing the two representative cross sections, while the second focuses on the micro dynamics drawn from the panel component. Transitions between formal and informal sector are explored. The third part aims at analyzing the perception of HBs' heads to assess the impact of the crisis. Then, the last section explores the changes as regards the problems faced by HBs, their interaction with the State and their outlook. In the conclusion, we determine some of the implications of the findings in terms of economic policies. This report can be usefully complemented by two companion papers: the first one presents the adjustment of the labor market and the informal economy nationwide, based on the LFS2007 & 2009 (Nguyen et al., 2010); the second one is a policy brief on the impact of the crisis on the informal sector in Hanoi and HCMC.
Keywords: Informal sector (Economics),Family business; Doanh nghiệp gia đình,Khu vực kinh tế không chính thức; Vietnam,Việt Nam,Vietnam,Việt Nam